Covid-19 makes it harder for GPs to offer the quiet listening that made all the difference to me. (22nd July 2021) - ,
Abstract : An anonymous patient explains how her GP used shared decision making to help her manage her distress. Quiet listening can empower patients to lead conversations about their own care, she says, but is threatened by the effects of covid-19, including more triage, remote care, and burnout among GPs